2008
DOI: 10.1614/wt-07-150.1
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Differences in Weed Susceptibility to Steam Injury

Abstract: Thermal weed control methods have been incorporated into weed control programs in organic and conventional production systems. Flaming is commonly used, but steaming has been proposed to increase efficiency of heat transfer to weeds and reduce the risk of fire. The objective of this research was to measure injury to leaves of plant species that differ in leaf morphology and to measure injury to plants at different stages of plant development. The study was conducted in a glasshouse and plants were exposed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…However, most of the younger weeds also regrew within a few weeks. These results support other recent findings suggesting that steam has differential effects on various weed species, with succulent weeds and grasses being poorly controlled compared with some other broadleaved weed species (Leon and Ferreira, 2008;Shrestha et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…However, most of the younger weeds also regrew within a few weeks. These results support other recent findings suggesting that steam has differential effects on various weed species, with succulent weeds and grasses being poorly controlled compared with some other broadleaved weed species (Leon and Ferreira, 2008;Shrestha et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…Ascard (1995) classified P. annua as very tolerant of flame weeding, because of its protected shoot meristems situated very near to the soil surface. Species with a prostrate growth habit, with protected meristems and narrow, thick leaves, such as S. procumbens , showed a greater tolerance to thermal treatments in studies by Ascard (1995) and Leon and Ferreira (2008). These traits reduce lethal heat transfer to the meristems and penetration into plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several plant morphological characteristics, including the presence of protective layers of hair and wax, lignification, condition of water status and leaf morphology (e.g. shape, width, thickness), have been reported as affecting tolerance to thermal weed control (Ascard, 1995; Hansson & Ascard, 2002; Leon & Ferreira, 2008). Control measures can result in the selection, leading to the predominance of tolerant species, particularly when using a single weed control method (Rask & Kristoffersen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal tools have been used for weed control. These tools include flaming (Ascard 1994), infrared (Ascard 1998) and ultraviolet-B radiation (Furness and Upadhyaya 2002), hot water (Hansson and Ascard 2002), microwave (Sartorato et al 2006), and steam (Kolberg and Wiles 2002;Leon and Ferreira 2008). The general principle behind these thermal weed control methods is to cause plant death by raising temperatures high enough to disintegrate the plants' cellular membranes (Sirvydas et al 2006).…”
mentioning
confidence: 99%
“…Some authors have reported that, to cause irreversible damage to cell membranes and thus plant cell death, the temperature should be at least 58 C (Daniell et al 1969;Vincent et al 2001). The plant damage, however, can depend on species (Leon and Ferreira 2008), plant size and density (Ascard 1994;Kolberg and Wiles 2002;Leon and Ferreira 2008), or plant morphological characteristics (Ascard 1995;Hansson and Ascard 2002;Leon and Ferreira 2008). Steam has been suggested to be more effective in killing plants than flame because 1 kg of wet water vapor releases 2,250 kJ of thermal energy, which is 3.7 to 11 times more than that released by 1 kg of propane used in flaming (Kerpauskas et al 2006).…”
mentioning
confidence: 99%